Metabolism and toxicokinetics of 1,4-dioxane in humans after inhalational exposure at rest and under physical stress - Göen, Thomas; Von Helden, Franziska; Eckert, Elisabeth; Knecht, Udo; Drexler, Hans; Walter, Dirk (Archives of Toxicology, 2016)
The present study investigated the toxicokinetics of 1,4-dioxane in humans exposed at rest and during physical stress. Eighteen volunteers were divided into three groups of six individuals each, who were exposed separately in three experiments to 20 ppm (73 mg/m(3)) 1,4-dioxane for 8 h. The first group was exposed at rest (Experiment 1), whereas the other groups performed exercises on a bicycle ergometer for 10 min every hour, corresponding to a physical exercise of 50 W (Experiment 2) and 75 W (Experiment 3), respectively. Blood samples were collected after 4 and 8 h, and all urine samples were collected over 24 h. The samples were analysed for 1,4-dioxane and its metabolite 2-(2-hydroxyethoxy)acetic acid (HEAA). The amount of urinary-eliminated HEAA increased during exposure and showed its maximum 9.8 ± 1.9 h after the beginning of exposure. The levels of 1,4-dioxane in blood and urine, however, barely rose above the limit of detection. Depending on the physical stress of the volunteers, the maximum elimination rate of HEAA in urine was significantly increased with 23.2 ± 7.7, 30.4 ± 7.2 and 41.8 ± 23.8 mg/h for Experiments 1, 2 and 3, respectively. Likewise, the cumulative HEAA excretion over 24 h increased with increasing physical stress; 53 ± 15 % of the theoretical inhaled 1,4-dioxane dose was excreted as HEAA in urine during the first 24 h. The average maximum level of HEAA ranged between 378 and 451 mg/g creatinine and increased with the applied physical stress. The half-life of HEAA was found to be 3.4 ± 0.5 h. Twenty-four hours after the beginning of the exposure, 31-51 mg HEAA/g creatinine were still detected in urine, indicating only a low accumulation of the metabolite during a working week. The study results revealed an increasing effect of the applied physical stress on the total eliminated amounts of HEAA as well as on the maximum HEAA levels at the end of exposure. For the estimation of biomonitoring equivalents to occupational exposure limits, this effect should be taken into account.
EVALuna2:9743